MATHEMATICAL MODELING OF IMMOBILISED Î‘-CHYMOTRYPSIN IN ACETONITRILE MEDIUM - Veeramuni, M. (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
Mathematical modeling of immobilized -chymotrypsin under kinetic control is discussed. The model is based on system of reaction diffusion equations containing a non-linear term related to enzyme reactor magazine. Modified Adomian decomposition method is employed to derive the general analytical expressions of dimensionless concentrations of acyl donor and nucleophile. Analytical results are compared with the numerical results and are found to be good in agreement. The model is able to predict reasonably well experimentally observed initial rate and nucleophile selectivity vs. enzyme loading profiles. The provided analytical solution leads to better understanding and new insight into problem. Â  Keywords: Kinetically controlled peptide synthesis; Nucleophile; Internal diffusion and reaction; Non-linear equations; Modified Adomian decomposition method.